2019
DOI: 10.4187/respcare.07124
|View full text |Cite
|
Sign up to set email alerts
|

The 1-Minute Sit-to-Stand Test in Lung Transplant Candidates: An Alternative to the 6-Minute Walk Test

Abstract: BACKGROUND: The 6-min walk test (6MWT) is a well-established functional exercise capacity test in lung transplant candidates. This study aimed to investigate the construct validity of the 1-min sit-to-stand test (1-min STS) as a marker of exercise capacity and knee extensor strength in lung transplantation candidates. METHODS: We retrospectively analyzed data from consecutive subjects referred for lung transplantation evaluation to our institution between 2015 and 2018. RESULTS: 38 subjects were included. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 34 publications
1
23
0
6
Order By: Relevance
“…We placed less weight on the nal ve studies -either because the sample was people with ventilation rather than perfusion defects and the methodological quality was uncertain, or because methodological quality was considered to be poor on our risk of bias and applicability tool, though the ndings from all these additional studies were similar to the above ones. These studies were: Gruet et al (a prospective correlation study from France in 25 patients with cystic brosis, which concluded that the 1MSTST may be used as an alternative to the 6MWT and CPET for assessing exertional desaturation) [45]; Morita et al (a study in 23 patients with COPD which showed good correlation between various exercise desaturation tests) [46]; Kohlbrenner et al (a retrospective study from Switzerland in 38 lung transplant candidates which concluded that the 1MSTST is a safe alternative to 6MWT in such patients despite lower desaturation nadirs) [47]; Crook et al (a prospective study in 21 COPD patients which concluded that 1MSTST is a safe and accurate alternative to 6MWT); and Azzi et al (a retrospective study in 36 lung cancer patients whose main aim was to compare a 3-minute chair-to-rise test, 3MCTRT, with the CPET in terms of maximal exercise capacity but which also found high correlation with the level of oxygen desaturation achieved) [48].…”
Section: Validation Of Tests For Exertional Hypoxia In Conditions Othmentioning
confidence: 99%
“…We placed less weight on the nal ve studies -either because the sample was people with ventilation rather than perfusion defects and the methodological quality was uncertain, or because methodological quality was considered to be poor on our risk of bias and applicability tool, though the ndings from all these additional studies were similar to the above ones. These studies were: Gruet et al (a prospective correlation study from France in 25 patients with cystic brosis, which concluded that the 1MSTST may be used as an alternative to the 6MWT and CPET for assessing exertional desaturation) [45]; Morita et al (a study in 23 patients with COPD which showed good correlation between various exercise desaturation tests) [46]; Kohlbrenner et al (a retrospective study from Switzerland in 38 lung transplant candidates which concluded that the 1MSTST is a safe alternative to 6MWT in such patients despite lower desaturation nadirs) [47]; Crook et al (a prospective study in 21 COPD patients which concluded that 1MSTST is a safe and accurate alternative to 6MWT); and Azzi et al (a retrospective study in 36 lung cancer patients whose main aim was to compare a 3-minute chair-to-rise test, 3MCTRT, with the CPET in terms of maximal exercise capacity but which also found high correlation with the level of oxygen desaturation achieved) [48].…”
Section: Validation Of Tests For Exertional Hypoxia In Conditions Othmentioning
confidence: 99%
“…Dos 13 artigos, 10 eram estudos observacionais longitudinais [70][71][72][73][74][75]77,78,80,82 , dois observacionais de corte transversal 76,79 e um utilizou dados de ensaios clínicos 81 . Apenas dois foram realizados em indivíduos hospitalizados, sendo um no departamento de emergência 70 e outro em adultos mais velhos 77 .…”
Section: Teste De Sentar E Levantar (Tso)unclassified
“…Apenas dois foram realizados em indivíduos hospitalizados, sendo um no departamento de emergência 70 e outro em adultos mais velhos 77 . Quanto à execução do teste, foram utilizadas cadeiras de 48 cm 74,81 , 46 -48 cm 71 , 46 cm 75 , 45,7 cm 77 , 45 cm 78 , 43,2 cm 73 , 43 cm 79 , cadeira ajustável para manter os quadris a 90 graus 76,82 e sem apoio para os braços [70][71][72][73][74][75]79 . Em apenas três artigos os indivíduos puderam usar os braços 76,77,80 .…”
Section: Teste De Sentar E Levantar (Tso)unclassified
See 2 more Smart Citations